2021
DOI: 10.3389/fimmu.2021.730545
|View full text |Cite
|
Sign up to set email alerts
|

HLA-G1+ Expression in GGTA1KO Pigs Suppresses Human and Monkey Anti-Pig T, B and NK Cell Responses

Abstract: The human leukocyte antigen G1 (HLA-G1), a non-classical class I major histocompatibility complex (MHC-I) protein, is a potent immunomodulatory molecule at the maternal/fetal interface and other environments to regulate the cellular immune response. We created GGTA1-/HLAG1+ pigs to explore their use as organ and cell donors that may extend xenograft survival and function in both preclinical nonhuman primate (NHP) models and future clinical trials. In the present study, HLA-G1 was expressed from the porcine ROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 75 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…To inhibit direct NK cell cytotoxicity, Weiss et al generated hHLA-E/hB2M transgenic pigs and found that pig endothelium derived from these animals was protected against human NK cytotoxicity and inhibited NKsecreted IFN-g (24). Rao et al inserted an HLA-G1 transgene, encoding a non-classical MHC-I protein, to the porcine ROSA26 locus, and created GGTA1 -/-/hHLA-G1 pigs (25). In fibroblasts, transplantable organs, and islets, the positive expression of HLA-G1 plays a central role in immune suppression by lowering IFN-g production via T cells and proliferation of CD4 + and CD8 + T cells, B cells, and NK cells (25).…”
Section: Nk Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…To inhibit direct NK cell cytotoxicity, Weiss et al generated hHLA-E/hB2M transgenic pigs and found that pig endothelium derived from these animals was protected against human NK cytotoxicity and inhibited NKsecreted IFN-g (24). Rao et al inserted an HLA-G1 transgene, encoding a non-classical MHC-I protein, to the porcine ROSA26 locus, and created GGTA1 -/-/hHLA-G1 pigs (25). In fibroblasts, transplantable organs, and islets, the positive expression of HLA-G1 plays a central role in immune suppression by lowering IFN-g production via T cells and proliferation of CD4 + and CD8 + T cells, B cells, and NK cells (25).…”
Section: Nk Cellsmentioning
confidence: 99%
“…Rao et al inserted an HLA-G1 transgene, encoding a non-classical MHC-I protein, to the porcine ROSA26 locus, and created GGTA1 -/-/hHLA-G1 pigs (25). In fibroblasts, transplantable organs, and islets, the positive expression of HLA-G1 plays a central role in immune suppression by lowering IFN-g production via T cells and proliferation of CD4 + and CD8 + T cells, B cells, and NK cells (25). To reduce xenoantigen expression and thus reduce the recipient's immune response, Fu et al generated GGTA1 -/-/B2M -/-/major histocompatibility complex class II transactivator (CIITA -/-) triple-knockout pigs, named GBC-21, by CRISPR/Cas technology and found that the resulting elimination of swine leukocyte antigen class I could effectively alleviate xenogeneic immune responses and prolong pig organ survival (26).…”
Section: Nk Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes the expression of Human leukocyte antigen G1 (HLA-G1), a non-classical class I major histocompatibility complex (MHC-I) protein that pays an important role in the maintenance of maternal-fetal tolerance. GKTO/HLAG1+ pigs have been developed and used as islet cell donors with the objective of extending xenograft survival and function in both preclinical NHP models and future clinical trials ( 128 ). GTKO/HLAG1+ pigs were shown to modulate the immune response by lowering IFN-γ production by T cells and proliferation of CD4 + and CD8 + T cells, B cells and NK cells, as well as by augmenting phosphorylation of Src homology region 2 domain-containing phosphatase-2 (SHP-2), which plays a central role in immune suppression.…”
Section: Outcome Of Genetically Modified Pigs As Islet Donors In Nhp ...mentioning
confidence: 99%
“…GTKO/HLAG1+ pigs were shown to modulate the immune response by lowering IFN-γ production by T cells and proliferation of CD4 + and CD8 + T cells, B cells and NK cells, as well as by augmenting phosphorylation of Src homology region 2 domain-containing phosphatase-2 (SHP-2), which plays a central role in immune suppression. Islets isolated from GTKO/HLA-G1+ genetically engineered pigs and transplanted into streptozotocin-diabetic nude mice restored normoglycemia, suggesting that the expression of HLA-G1 did not interfere with their ability to reverse diabetes ( 128 ). Using CRISPR/Cas9, it is possible to target the cellular immune system at multiple levels.…”
Section: Outcome Of Genetically Modified Pigs As Islet Donors In Nhp ...mentioning
confidence: 99%